Apakah Shelter Bus Batik Solo Trans Aksesibel Bagi Penyandang Disabilitas? - Endang Sri Wahyuni (Jurnal Keterapian Fisik, 2019)
Background: Availability of facilities and infrastructure for public facilities that facilitate accessibility for people with disabilities is very important. The basic thing for increasing the independence of people with disabilities is the availability of adequate public service facilities. One of the supporting facilities to fulfill public facilities is the Batik Solo Trans bus shelter. The purpose of this study is to analyze the accessibility of people with disabilities in assessing the assistance of Trans Solo Batik buses in Surakarta City. Method: This type of research is explorative qualitative research. Methods of interviewing, observation, and documentation. Data is obtained through interviews with persons with physical and mental disabilities. The data analysis technique uses the triangulation method. Results: Persons with disabilities are still experiencing difficulties in accessing due to architectural barriers. Design shelter still does not meet established accessibility standards. Conclusion: Shelter Solo Trans Batik buses in Surakarta City are not accessible for people with disabilities. The limited accessibility for people with disabilities requires further study in a design that is in accordance with the principles of ergonomics and accessibility in order to accommodate the public interest in general and people with disabilities in particular.